Textile Import to the Territory of Rus in the IX – First Third of the XIII Century according to Archaeological Data - Elizaveta M. Kalugina (Археология евразийских степей)
The article deals with the finds of archaeological textiles of IX - the first third of XIII centuriy found on the territory of Rus, which are identified as imported products. Based on archaeological data, the range of imported textiles and the ways of their use are analyzed. The attention is also given to the issue of specific technological characteristics of textiles that help to clarify their origin. This research demonstrated that quite a large amount of foreign textiles was imported into Rus; this included fabrics, silk and gold threads, and sometimes finished textile products. At the same time archaeological data indicates that the local population used silk and gold-woven textiles from the Mediterranean, Central Asia, the Far East, and China. The gold threads came from Byzantium, Western Europe, and the countries of the East. Besides, gold-woven ribbons and woolen fabrics manufactured in Western Europe were imported into the Rus. The use of cotton is not typical for this period, but there are single finds of such textiles, similar to the products of Central Asia, Turkey, Persia or India. The study of textile finds confirms the existence of trade relations between Rus and other countries in the IX – first third of the XIII century.